2013 Benjamin Franklin Medal in Physics presented to Alexander Dalgarno†. Issue 7 (July 2015) - Szalewicz, Krzysztof
Abstract Studies of outer space have fascinated humanity for ages and are of importance for understanding life on Earth. Molecular astrophysics, developed into a rigorous field of investigation by Alexander Dalgarno beginning in the 1960s, studies radiation emitted or absorbed by molecules in space to expand our knowledge concerning the structure and dynamics of the universe. More than one hundred molecules have been detected in interstellar space and most of these molecules have large numbers of observable transitions, so the amount of information provided is huge. Dalgarno has used this information to develop models of interstellar space, in particular of molecular clouds. These models account for the heating and cooling mechanisms, excitations and de-excitations of molecules (in particular of H2), magnetohydrodynamic shockwaves, formation and destruction of molecules, and chemical reactions in space.